Animals Comouflage - Powzyk, Joyce; Nang ChanYeema (New York, USA Bradbury Press, 1990)
Introduces general ways animals camouflage themselves, such as coloration, mimicry, and disguise, and discusses how specific animals protect themselves using these techniques.
Keywords: Juvenile Nonfiction